2011
DOI: 10.1002/chem.201003744
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase‐Mediated Synthesis of a DNA–(Enzyme)n Probe for Highly Sensitive DNA Detection

Abstract: A new synthetic strategy for DNA-enzyme conjugates with a novel architecture was explored using a natural cross-linking catalyst, microbial transglutaminase (MTG). A glutamine-donor substrate peptide of MTG was introduced at the 5-position on the pyrimidine of deoxyuridine triphosphate to prepare a DNA strand with multiple glutamine-donor sites by polymerase chain reaction (PCR). A substrate peptide that contained an MTG-reactive lysine residue was fused to the N terminus of a thermostable alkaline phoshatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 43 publications
1
43
0
2
Order By: Relevance
“…Once again, this work remains at the level of in vitro experimentation in a model system and has yet to be tested in vivo . TGase-mediated labeling has also been further expanded to label biological macromolecules other than proteins, such as DNA and RNA [88,89] (Figure 6C). Nucleic acid hybridization techniques make it possible to detect the expression pattern of a particular gene, which may be indicative of a disease.…”
Section: Protein Labelingmentioning
confidence: 99%
“…Once again, this work remains at the level of in vitro experimentation in a model system and has yet to be tested in vivo . TGase-mediated labeling has also been further expanded to label biological macromolecules other than proteins, such as DNA and RNA [88,89] (Figure 6C). Nucleic acid hybridization techniques make it possible to detect the expression pattern of a particular gene, which may be indicative of a disease.…”
Section: Protein Labelingmentioning
confidence: 99%
“…[2] To gain insight into the mechanisms by which DNA polymerases are able to process modified nucleotides despite their active sites being strictly defined, functional and structural studies have been performed. It has been shown that nucleotides bearing small-molecule modifications such as affinity, [3] spin, [4] and redox labels; [5] dyes; [2a] amino acids; [6] nucleosides; [7] or short oligonucleotides [8] can be used as substrates for DNAr eplication by DNAp olymerases.…”
mentioning
confidence: 99%
“…All lipid substrates were manually synthesized on Fmoc-Gly-Alko resin with an Fmoc strategy (Scheme S1 in the Supporting Information). [14] The identification of these lipid substrates was confirmed by reversedphase (RP)-HPLC ( Figure S1 in the Supporting Information) and matrix-assisted laser desorption/ionization time-offlight mass spectrometry (MALDI-ToF MS).Although a variety of artificial substrates for MTG-mediated protein functionalization are available, [8][9][10] no lipid substrates have been reported. First, monodansylcadaverine (MDC), which is known as an acyl acceptor substrate for MTG, [8b] was employed as a conjugation partner to test the reactivity of MTG for the lipid substrates.…”
mentioning
confidence: 99%
“…Among different types of TGases, we selected microbial TGase from Streptomyces mobaraensis (MTG), which is one of the most well-studied and robust TGases. [7] Many researchers have achieved MTG-mediated protein labeling of functional molecules (e.g., fluorophore, [8] ligand, [9] nucleic acids [10] ) and MTG has been widely recognized as a powerful molecular stapler in the creation of artificial proteins. However, the use of MTG for lipid modification of proteins has not been reported.To realize MTG-mediated protein lipidation, we first had to design and synthesize lipid substrates.…”
mentioning
confidence: 99%